A Miniature Graphene-based Biosensor for Intracellular Glucose Measurements. (20th August 2015) - Hasan, Kamran ul; Asif, Muhammad H.; Hassan, Muhammad Umair; Sandberg, Mats O.; Nur, O.; Willander, M.; Fagerholm, Siri; Strålfors, Peter
Abstract: We report on a small and simple graphene-based potentiometric sensor for the measurement of intracellular glucose concentration. A fine borosilicate glass capillary coated with graphene and subsequently immobilized with glucose oxidase (GOD) enzyme is inserted into the intracellular environment of a single human cell. The functional groups on the edge plane of graphene assist the attachment with the free amine terminals of GOD enzyme, resulting in a better immobilization. The sensor exhibits a glucose-dependent electrochemical potential against an Ag/AgCl reference microelectrode which is linear across the whole concentration range of interest (10 – 1000 μM). Glucose concentration in human fat cell measured by our graphene-based sensor is in good agreement with nuclear magnetic resonance (NMR) spectroscopy.